Biomechanical analysis of different techniques for residual bone defect from tibial plateau bone cyst in total knee arthroplasty - Liu, Dehua; Miao, Zhuang; Zhang, Wenfei; Liu, Chuanwen; Du, Longzhuo; Zhu, Yuanlong; Luo, Yange; Zheng, Weibo; Zhou, Jianli; Liu, Peilai; Li, Xuezhou; Li, Ming (Frontiers in Bioengineering and Biotechnology, 2024)
In patients with tibial plateau bone cysts undergoing total knee arthroplasty (TKA), bone defects commonly occur following tibial plateau resection. Current strategies for addressing these defects include bone grafting, bone cement filling, and the cement-screw technique. However, there remains no consensus on the optimal approach to achieve the best surgical outcomes. This study aims to evaluate the most effective repair method for residual bone defects following tibial plateau bone cyst repair during TKA from a biomechanical perspective.The treatment options for tibial plateau bone defects were classified into four categories: no treatment, cancellous bone filling, bone cement filling, and the cement-screw technique. Finite element analysis (FEA) was employed to evaluate stress distribution and displacement across the models for each treatment group. In addition, static compression mechanical tests were used to assess the displacement of the models within each group.Results: FEA results indicate that when employing the cement-screw technique to repair tibial plateau bone defects, the maximum stress on the prosthesis and the cement below the prosthesis is minimized, while the maximum stress on the cancellous bone is maximized. And the displacement of each component is minimized. Biomechanical tests results further demonstrate that the displacement of the model is minimized when utilizing the cement-screw technique for tibial plateau bone defects.Using cement-screw technique in treating residual tibial bone defects due to bone cysts in TKA offers optimal biomechanical advantages.